2013
DOI: 10.1149/2.046312jes
|View full text |Cite
|
Sign up to set email alerts
|

Ta Surface Chemistry in Aqueous Solutions and the Possible Formation of TaTe2and TaS3

Abstract: This report discusses the reductive removal of Ta oxide electrochemically using cyclic voltammetry (CV), in-situ electrochemical scanning tunneling microscopy (EC-STM), and X-ray photoelectron spectroscopy (XPS). From CVs, it was shown that the longer a Ta electrode was maintained at potentials negative of −1.5 V, the more surface oxide that was reduced, as evidenced by increases in hydrogen evolution. Atomically-resolved EC-STM images were obtained after reduction at −1.8 V. The efficacy of Te at passivating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This observation readily implies that at more negative potentials the Ta in the electrodeposited film was reduced, which results in the formation of Ta suboxides with lower oxidation states of Ta. This is further consistent with the previous study by Stickney and co-workers where they showed that the surface oxide layer on the tantalum foil can be reduced in aqueous solutions at potentials below −1.5 V . Thus, electrodeposition was performed at −1 V vs Ag/AgCl.…”
Section: Resultsmentioning
confidence: 79%
“…This observation readily implies that at more negative potentials the Ta in the electrodeposited film was reduced, which results in the formation of Ta suboxides with lower oxidation states of Ta. This is further consistent with the previous study by Stickney and co-workers where they showed that the surface oxide layer on the tantalum foil can be reduced in aqueous solutions at potentials below −1.5 V . Thus, electrodeposition was performed at −1 V vs Ag/AgCl.…”
Section: Resultsmentioning
confidence: 79%
“…Their crystals can exhibit ionic, covalent, and metallic bonding interactions. [26][27][28][29][30][31] In particular, the relatively low electronegativity of tellurium in transition metal tellurides frequently leads to complex competition between metals and nonmetals for the valence electrons and, as a consequence, to valence electron localizations. It is interesting to note that TaTe 2 has been reported to have a distorted 1T structure with space group C2/m.…”
Section: Introductionmentioning
confidence: 99%